2020
DOI: 10.1038/s41598-020-61859-6
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of negative electronic compressibility and capacitance enhancement in lightly-doped metal oxide Bi0.95La0.05FeO3 by quantum capacitance model

Abstract: Light-sensitive capacitance variation of Bi 0.95 La 0.05 feo 3 (BLfo) ceramics has been studied under violet to UV irradiation. The reversible capacitance enhancement up to 21% under 405 nm violet laser irradiation has been observed, suggesting a possible degree of freedom to dynamically control this in high dielectric materials for light-sensitive capacitance applications. By using ultraviolet photoemission spectroscopy (UpS), we show here that exposure of BLfo surfaces to UV light induces a counterintuitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The obtained behavior is a typical characteristic of dielectrics with low mobility. [ 11 ] The dielectric constant values for all the films are higher at lower frequencies, which rapidly decreases at higher frequencies and becomes saturated at 1 MHz. [ 8 ] Dielectric constant values are higher at lower frequencies because of contribution of all types of polarization, which is also suggested and agreed with Koop's phenomenological theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained behavior is a typical characteristic of dielectrics with low mobility. [ 11 ] The dielectric constant values for all the films are higher at lower frequencies, which rapidly decreases at higher frequencies and becomes saturated at 1 MHz. [ 8 ] Dielectric constant values are higher at lower frequencies because of contribution of all types of polarization, which is also suggested and agreed with Koop's phenomenological theory.…”
Section: Resultsmentioning
confidence: 99%
“…Nathabumroong et al reported 19% dielectric enhancement in the presence of UV radiation for the lanthanum doped bismuth ferrite (BLFO) ceramic. [ 11 ] More recently, Jaiban et al studied dielectric enhancement in barium calcium zirconate titanate (BCZT)‐based ceramic and achieved 60% dielectric enhancement in the presence of UV illumination. [ 10 ] Jaiban et al showed the influence of acceptor dopants, copper, magnesium, and iron, on electrical and optical properties of Ba 0.7 Ca 0.3 TiO 3 ceramics and tuned the electrical properties under UV illumination.…”
Section: Introductionmentioning
confidence: 99%
“…It is accompanied by an increase in the intensity of the sub-gap state peak around 1.3 eV (inset in Figure d). Looking at previous studies, we consider that this sub-gap defect state is most likely associated with oxygen vacancies at the surface. The surface oxygen vacancies on Cu 2 O electrodes play an important role in the separation of photogenerated electron–hole pairs and in the improvement of redox behavior involving photocapacitive performance. When Cu 2 O is irradiated by light greater than its optical bandgap (valence band maximum (VBM) shift to EF), electron–hole pairs are generated (eq ). Then, the photogenerated electrons are trapped by surface oxygen vacancies (peak at 1.3 eV). ,, These charges captured momentarily by surface oxygen vacancies are then readily transmitted to the Cu substrate , (see schematic in Figure S14).…”
Section: Discussionmentioning
confidence: 99%